High insecticide resistances levels in Anopheles gambiaes s.l. in northern Uganda and its relevance for future malaria control - Echodu, Richard; Iga, Julius; Oyet, William Samuel; Mireji, Paul; Anena, Juliet; Onanyang, David; Iwiru, Tereza; Lutwama, Julius Julian; Auma Opiyo, Elizabeth (BMC research notes, 2020)
The aim of the study was to determine the level of insecticide resistance and diversity in Anopheles mosquitoes in northern Uganda. Standard WHO insecticide susceptibility test assays were used to test for susceptibility to 0.5% malathion, 0.1% bendiocarb, 0.05% deltamethrin and 0.75% permethrin on 3–5 day old generation one progeny. We also screened for species diversity and knockdown resistance using PCR assay. Results: Anopheles gambiae s.s. is the predominant malaria vector in northern Uganda followed by An. arabiensis. An. gambiae s.s. was susceptible to malathion and bendiocarb with the observed mortality rate of 100% and 98–100% observed respectively while very high resistance was observed with deltamethrin and permethrin. Minimal KDReastern variant homozygous forms of 8.3% in An. gambiae s.s. were detected in Oyam district. In conclusion, this study confirms that An. gambiae s.s. females are susceptible to malathion and bendiocarb while high intensity of resistance was observed with deltamethrin and permethrin in the same area. Use of carbamate and organophosphate insecticides bendiocarb and malathion for indoor residual spraying activities in northern Uganda is highly recommended since high levels of pyrethroids resistance (deltamethrin and permethrin) was detected in the area.
Keywords: Pyrethroid resistance; Malathion; Bendiocarb; Deltamethrin and permethrin; Uganda